Effect of Metformin Therapy on Low Density Lipoprotein (LDL) Levels in Type 2 Diabetes Mellitus Patients at Undata Hospital in Palu City Central Sulawesi: Efek Terapi Metformin terhadap Level Low Density Lipoprotein (LDL) pada Pasien Diabetes Mellitus Tipe 2 pada RS Undata di Kota Palu Sulawesi Tengah - Mukaddas, Alwiyah; Rumi, Amelia; Yulianti, Tri (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2022)
Background: Metformin, which can control blood glucose levels, can reduce LDL levels in type 2 DM patients. Objectives: To determine the mean value of pre and post LDL in type 2 DM patients after receiving metformin therapy for three months. Methods: This study used a cross-sectional study with a prospective approach, It was done by conducting pre and post examination of LDL levels using metformin. This study was analyzed using the SPSS Wilcoxon statistical test. The total sample that met the inclusion and exclusion criteria was 18 respondents. Results: This study used a single metformin value (sig = 0.000 <0.05) with a baseline mean value of 148.22 mg / dL and an evaluation of 133.56 mg / dL where the difference in reduction was 14.66 mg / dL. Conclusion: There was a decrease in LDL levels in type 2 DM patients after using metformin for three months.